Studi Kajian: Workplace Communication Skills - Davina Meta Mutiara; Diandri Nadja; Syakila Putri Alysva; Shafa Salsabila; Mada Aditia Wardhana (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2025)
Workplace Communication Skills (WCS) are proven to be a critical foundation for a company's competitive advantage in the context of a dynamic global market. This study successfully conceptualizes a map of WCS that integrates fundamental social competencies—from verbal, non-verbal, written, and electronic communication to interpersonal skills, negotiation, presentation, and digital rhetoric—with the demands of the Fourth Industrial Revolution. Through a systematic analysis of 44 selected articles from the DOAJ, this study identifies the causal mechanisms through which WCS mastery shapes corporate excellence via three main pathways: enhancing operational efficiency through effective team collaboration, strengthening market orientation through the ability to present value, and preventing organizational issues such as psychological workplace violence. The findings confirm that the integration of digital technology in WCS development not only facilitates innovative training and assessment methods but also directly supports the creation of a workforce that is competent both technically and socially. Therefore, strategic investment in WCS is a prerequisite for building superior human capital capable of delivering sustainable profits and long-term competitive strength for organizations.